TINJAUAN TEKNIK PEMBUATAN TAS YANG MENGGUNAKAN MATERIAL BATOK KELAPA - Syahrul Ramadhan; Ali Ramadhan (Universitas Mercu Buana, 2021)
A bag is an object that is often used by all groups, both lower and upper classes. A bag is a tool for carrying an item of luggage Aside from being a place to store an item, a bag is also an important part of the fashion world. Starting from the shape of a bag and the material in the bag that makes bags increasingly become an important part of the fashion world. The types of bags using one of the materials such as coconut shells. Coconut shells are often used as a traditional craft, with natural coconut shell motifs making the patterns look beautiful. This coconut shell material has properties that are quite strong and beautiful in abstract coconut shell patterns. Nowadays, coconut shells are made into a bag material to attract bag users because of their uniqueness.